Gender and Power Relations in a Malagasy Congregational Asset-Based Community Development Project: Research Article - Rakotoarison, Zo Ramiandra (Religion & development, 2024)
Managing power relations is a development concern, and this study adds to research addressing questions of power and gender balance in local community development projects. It analyses power relations and gender roles within a Malagasy congregational asset-based community development project called “Use Your Talents”. In local communities as well as in larger society, power relations and gender injustice are interlinked. This paper is part of a qualitative study with data collected in 2018 at four Lutheran congregations in Madagascar with forty-one female and male informants. In analysing the interview, the following themes emerged: “power over” in favour of adult men, ‘power to’ that differentiates between women’s and men’s possibilities and limitations, ‘power with’ as collaboration between women, men and young people and activities based on gender and age, and “power within” from God and from skills based on gender. The study revealed that Use Your Talents mostly emphasises the ‘power within/with’, and where power is exercised ‘to and over’, it is mainly adult men exercising power. The study also found that women contributed significantly to congregational community development projects. The study concludes that the church provides both women and men opportunities for development through the Use Your Talents approach, but they exercise different aspects of power. This is reinforced by Use Your Talents and affected their roles, relations and activities in congregational community development. The difference in power favours adult men, while limiting economic and social possibilities for women.